2006
DOI: 10.1098/rsbl.2006.0576
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body temperature influence the scaling of and aerobic scope in mammals

Abstract: Debate on the mechanism(s) responsible for the scaling of metabolic rate with body size in mammals has focused on why the maximum metabolic rate ( _ V O 2 max ) appears to scale more steeply with body size than the basal metabolic rate (BMR). Consequently, metabolic scope, defined as _ V O 2 max /BMR, systematically increases with body size. These observations have led some to suggest that _ V O 2 max and BMR are controlled by fundamentally different processes, and to discount the generality of models that pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…First, as Gillooly & Allen (2007) themselves admit, their postulated effect of temperature on metabolic rate can explain only approximately 50% or less of the difference in b between the resting and maximally active conditions, if the most current and comprehensive datasets on mammals are examined (resting bZ0.68; active bZ0.87: see table 1). This is true even if the athletic species are removed from the sample (the scaling exponent for MMR is still relatively high: 0.85; Weibel et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…First, as Gillooly & Allen (2007) themselves admit, their postulated effect of temperature on metabolic rate can explain only approximately 50% or less of the difference in b between the resting and maximally active conditions, if the most current and comprehensive datasets on mammals are examined (resting bZ0.68; active bZ0.87: see table 1). This is true even if the athletic species are removed from the sample (the scaling exponent for MMR is still relatively high: 0.85; Weibel et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, these deviations have been predicted by MTE in multicellular plants (West et al 1999b, Enquist et al 2007) and animals (West et al 1997). For example, with respect to mammals, Gillooly and Allen (2007) recently showed that the steeper size‐dependence of maximum metabolic rate is attributable to greater increases in muscle temperature for large mammals (e.g.>6°C for a horse) than for small mammals (e.g.<1°C for a rat) during exercise. In other cases, deviations from ¾ power scaling are expected, but have not yet been integrated into the theory.…”
Section: Individual‐level Mechanismsmentioning
confidence: 99%
“…An example of when the choice of FAS or AAS may affect interpretation of results is when aerobic scope is compared across a range of body sizes and life stages (Bishop 1999;Gillooly and Allen 2007;Glazier 2009;Weibel and Hoppeler 2005). Relatively few studies have quantified changes in both SMR and MMR over orders of magnitude of body sizes for a single species (Brett 1965;Clark et al 2012;Killen et al 2007).…”
Section: Introductionmentioning
confidence: 99%